Autonomy in Aceh-Indonesia, from Armed Conflict to Regulation Conflict - Muhammad Siddiq Armia (Proceedings of AICS - Social Sciences, 2017)
The Memorandum of Understanding (MoU) in Helsinki in 2005, the Government of Aceh agrees to unconditionally accept the Act of Government of Aceh, delivering the principles of special autonomy and ending the 30-years conflict. The Act orders explicitly and implicitly to legislate some bylaws for implementing the norms of autonomy. Despite passing bylaws, both Government of Aceh and Central Government have involved in endless regulation conflict, including land and flag bylaw. This article uses black-letter law approach as research method, focusing on several government official texts, and case law happening during this conflict.